Spatial Generation, Degeneration, and Regeneration Aerotaxis Mechanisms Toward Bio-Integrated Design - Mathilda, Gita Rahma; Andikabina, Ariko; Suryantini, Rini; Atmodiwirjo, Paramita (Jurnal Linears, 2025)
This study aims to explore spatial mechanism developed within bio-integrated design through exploring the complex natural processes of "aerotaxis". The investigation of aerotaxis employs the Azospirillum brasilense by observing its behavior and interaction within its habitat and to identify possible spatial mechanisms. Azospirillum brasilense, a microorganism known for aiding plant growth and nitrogen fixation, demonstrates a symbiotic relationship with its host, inspiring innovative architectural approaches. By tracing its movement, living pattern and traces show distinct mechanisms such as the generation, degeneration, and regeneration of space. This framework redefines architectural spatial and material concepts that are arguably crucial for a bio-integrated design. The study shows that the aerotaxis mechanism generates spaces as a dynamic continuum where materials are synthesized, consumed, and renewed in balance. Understanding the biological processes offers an alternative framework in designing space structures that align with nature's complex systems. Such an approach provides a pathway to foster a deeper intertwining between architecture and biological processes. As a result, the study highlights the potential of bio-based design mechanisms as a regenerative practice.